Studi Morfometrik Kepiting Rajungan (Portunus Pelagicus) - Umi Kalsum; Rivo Hasper Dimenta (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2023)
This study aims to reveal the morphometric characteristics crab P. pelagicus in the Sei Berombang estuary waters. The purposive sampling method used to determining 3 sampling stations, sampling process was using trawl nets. The results showed that the P. pelagicus population at Station 1 dominated by small carapace, at stations 2 and 3 found the domination of larger size with juvenile and adult phases category. The morphometric characters of carapace width (CW) in blue/flower crabs ranged from 9.50 to 17.40 cm, left posterolateral carapace length (LPCL) ranged from 2.20-6.70 cm, left anterolateral carapace length (LACL) ranged from 1.30-6.50 cm, right anterolateral carapace length (RACL) ranged from 1.20-7.00 cm, frontal right width (FRMW) ranged from 1.50-3.70 cm, carapace length (CH) ranged from 3.70-7.00 cm, internal carapace width (ICW) ranged from 6, 30-14.10 cm, right orbit (eye socket) width (ROW) ranged from 1.06-2.00 cm, left orbit (eye cavity) width (LOW) ranged from 1.12-2.10 cm, carapace width (CW) ranged from 9.50-17.40 cm, left posterolateral carapace length (LPCL) ranged from 2.20-6.70 cm, and left anterolateral carapace length (LACL) ranged from 1.30-6.50 cm. Conclusion, The morphometric characters of male and female P. pelagicus in the Sei Berombang waters were found to vary spatially and temporally. Kata Kunci: Characteristic Morphology, Identification, Morphometric, P. pelagicus